2022
DOI: 10.2217/fon-2021-1647
|View full text |Cite
|
Sign up to set email alerts
|

KEYNOTE-522, IMpassion031 and GeparNUEVO: changing the paradigm of neoadjuvant immune checkpoint inhibitors in early triple-negative breast cancer

Abstract: Stage I–III triple-negative breast cancer accounts for approximately 15–20% of new diagnoses of early breast cancer. Novel systemic treatment options have recently been assessed as part of the neoadjuvant approach, such as the addition of immune checkpoint inhibitors to cytotoxic chemotherapy. However, several questions remain unanswered, including the identification of predictors of response to immunotherapy in this setting, and further efforts aimed at identifying reliable predictors and clarifying the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…However, recent evidence suggests lactate production and the resultant acidification of the tumor microenvironment play crucial roles in angiogenesis, invasion, metastasis, and immune evasion in certain cancer (19,30,32). Intriguingly, further studies have validated that lactylation occurs in both histone and nonhistone proteins and that protein lysine lactylation is vital for lactate function (4,14,22). Although histone lactylation has been primarily associated with non-neoplastic diseases (33,34), its presence in cancer has been infrequently reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent evidence suggests lactate production and the resultant acidification of the tumor microenvironment play crucial roles in angiogenesis, invasion, metastasis, and immune evasion in certain cancer (19,30,32). Intriguingly, further studies have validated that lactylation occurs in both histone and nonhistone proteins and that protein lysine lactylation is vital for lactate function (4,14,22). Although histone lactylation has been primarily associated with non-neoplastic diseases (33,34), its presence in cancer has been infrequently reported.…”
Section: Discussionmentioning
confidence: 99%
“…According to data from the International Agency for Research on Cancer (IARC) of the World Health Organization (WHO), breast cancer (BC) has now become the most common malignant tumor globally, surpassing lung cancer ( 1 , 2 ). Triple-negative breast cancer (TNBC), characterized by the absence of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) expression, represents approximately 15%–20% of all BC cases ( 3 , 4 ). TNBC poses a greater clinical challenge compared to other BC types due to its higher rates of recurrence and metastasis, shorter median survival, and poorer prognosis ( 3 , 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another FDA-approved regimen is atezolizumab with CT based on the results of the IMPASSION 130 trial (NCT02425891) for PD-L1-expressing metastatic TNBC, which demonstrated that atezolizumab with nanoparticle albumin-bound (nab)-paclitaxel prolonged PFS in patients with PD-L1-expressing metastatic TNBC compared to patients receiving placebo plus nab-paclitaxel. A variety of clinical trials are still ongoing to study alternative combinations of IBCs with other drugs in luminal tumors, HER2+ and TNBC [ 12 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ].…”
Section: Immunotherapy In Breast Cancermentioning
confidence: 99%
“…Favorably, there was a statistically significant tendency for improved three-year survival, including invasive disease-free survival (iDFS), distant disease-free survival (DDFS), overall survival (OS), and no new safety signals occurring. In the durvalumab group and placebo group, iDFS was 85.6% vs. 77.2% ( p = 0.036), DDFS was 91.7% vs. 78.4% ( p = 0.005), and OS was 95.2% vs. 83.5% ( p = 0.006), respectively [ 34 , 35 , 36 ].…”
Section: Pd-1/pd-l1 Inhibitors Plus Neoadjuvant Chemotherapymentioning
confidence: 99%
“…The study suggested that the addition of immunotherapy reduced RCB scores and improved EFS. Based on a series of promising results and the relatively mild side effects of pembrolizumab from KEYNOTE-522 and other studies, both the European Medicines Agency (EMA) and the FDA approved joining pembrolizumab and chemotherapy for neoadjuvant therapy and subsequent adjuvant therapy, establishing the first immunotherapy regimen approved in high-risk, early-stage TNBC [ 36 , 43 ].…”
Section: Pd-1/pd-l1 Inhibitors Plus Neoadjuvant Chemotherapymentioning
confidence: 99%